Student’s access and performance in the Portuguese Higher Education: Issues of gender, age, socio-cultural background, expectations, and program choice (Avaliação: Revista da Avaliação da Educação Superior, 2019)
The purpose of this article is to characterize and contribute to the debate on the democratization of Portuguese higher education, both in terms of access and the performance of students enrolled in a public university. The analyses concern the sociodemographic characteristics and schooling trajectory of the 2,697 students enrolled for the first time in the University of Minho in the academic year 2015/16. The relationships between such characteristics and the choice of program, expectations regarding higher education, the criteria of admission, and the association with their permanence and performance in the first year of studies are explored as well. Several statistical tests were applied, such as those based on multivariate analysis of variance, chi-squared test for the independence between variables, or the t-Student test for the comparison of means of two independent samples. Results suggest that student’s gender, socio-cultural background and schooling trajectory are related to the choice of the programe, university entrance score and the entrance option. The multivariate analysis of variance of student’s grade point average at the end of the first year suggests the influence of the interaction between the fixed term of scientific-disciplinary area of the program attended and the program option of access to higher education. We did not find any statistically significant association between socio-cultural background and permanence in higher education; i.e, the socio-cultural origin of the students does not seem to influence the decision to abandon, suspend or transfer program, at least during their first year of studies. Our findings suggest student’s resilience and/or institutional action meaning a step further on the path for social equity in the Portuguese higher education.